From the gut to the heart: L. plantarum and inulin administration as a novel approach to control cardiac apoptosis via 5-HT2B and TrkB receptors in diabetes. Issue 1 (January 2021) - Sefidgari-Abrasi, Safa; Roshangar, Leila; Karimi, Pouran; Morshedi, Mohammad; Rahimiyan-Heravan, Marziyeh; Saghafi-Asl, Maryam
Summary: Background & aims: Type 2 diabetes mellitus, as a metabolic disorder, can lead to diabetic cardiomyopathy, identified by cardiomyocyte apoptosis and myocardial fibrosis. Brain-derived neurotrophic factor (BDNF) and serotonin are two neurotransmitters that can control cardiomyocyte apoptosis and myocardial fibrosis through their cardiac receptors. In the present study, we investigated the impacts of L . plantarum and inulin supplementation on the inhibition of cardiac apoptosis and fibrosis by modulating intestinal, serum, and cardiac levels of serotonin and BDNF as well as their cardiac receptors. Methods: Diabetes was induced by a high-fat diet and streptozotocin in male Wistar rats. Rats were divided into six groups and were supplemented with L . plantarum, inulin or their combination for 8 weeks. Finally, the rats were killed and levels of intestinal, serum, and cardiac parameters were evaluated. Results: Concurrent administration of L . plantarum and inulin caused a significant rise in the expression of cardiac serotonin and BDNF receptors (P < 0.001) as well as a significant fall in cardiac interstitial and perivascular fibrosis (P < 0.001, both) and apoptosis (P = 0.01). Moreover, there was a strong correlation of cardiac 5-Hydroxytryptamine 2B (5-HT2B) and tropomyosin receptor kinase B (TrkB) receptors with interstitial/perivascular fibrosis and apoptosis (P < 0.001, both). Conclusions/interpretation: Results revealed beneficial effects of L . plantarum, inulin or their combination on intestinal, serum, and cardiac serotonin and BDNF accompanied by higher expression of their cardiac receptors and lower levels of cardiac apoptotic and fibrotic markers. It seems that L . plantarum and inulin supplementation could be considered as a novel adjunct therapy to reduce cardiac complications of type 2 diabetes mellitus.